2006
DOI: 10.1177/152692480601600113
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Death Criteria and Organ Donation among Healthcare Personnel and the General Public

Abstract: Both general and ethical education may serve to guide policy and facilitate family member requests and informed consent dialogues. Furthermore, helping families to understand and accept not only medical and legal criteria for determining death, but also ethical criteria for withdrawing life support may help them be more comfortable with their decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 38 publications
(37 reference statements)
2
61
0
4
Order By: Relevance
“…Other authors have published reviews on this subject, but these generally examine a part of the whole picture and are limited to publications in English. 8 If the present study had reviewed only papers in English, 12% of the total would had been excluded; that is, those reporting research in Spain and Brazil. More papers were found in Spanish than in Portuguese.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have published reviews on this subject, but these generally examine a part of the whole picture and are limited to publications in English. 8 If the present study had reviewed only papers in English, 12% of the total would had been excluded; that is, those reporting research in Spain and Brazil. More papers were found in Spanish than in Portuguese.…”
Section: Discussionmentioning
confidence: 99%
“…7 Their views and opinions on the donation process, for example, have facilitated the identification of potential donors and thus are highly influential in the way people think about the process. [8][9][10] Although empirical studies on health care personnel's point of view have been conducted, few studies have reviewed the literature as a whole. 11 Some reviews have compared the knowledge and attitudes of nurses toward organ donation across countries; 9 others have synthesized the literature on the attitudes of these professionals towards brain death and organ donation; 8 some others have reviewed research on attitudes of medical personnel toward organ donation in the case of cardiac death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 According to the study a higher number of medical students 38 (74%), believed brain death to be an important criterion for accepting organ donation as opposed to some studies where medical students were unaware of the "Dead Donor Rule". 13 Anybody can pledge their organs by registering with various national organizations working in order to promote the awareness of organ donation in India (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear relation between this fear and the discovery of brain death. [14][15][16][17][18] Studies of the Spanish population have shown that the lack of understanding of the brain death concept and the fear of apparent death in the donation process was at one point as high as 70% to 80%. 19 Although these data have improved, presently, nearly 50% of the Spanish population do not know this concept, and its misconception continues to be an independent factor affecting attitude toward deceased organ donation.…”
Section: Discussionmentioning
confidence: 99%